Hepatoprotectors to build strength in athletes - Rodichkin, P. V.; Ponomarev, G. N.; Pupkov, P. V.; Orlov, A. S. (Theory and Practice of Physical Culture, 2020)
Modern physical education service system reports the growing popularity of the muscular mass and strength building physical practices including the training machines assisted ones, with weights, rubber expanders, suspension systems, gymnastic equipment and own weight used in trainings. Sport science knows many agents of effect on the muscular fatigue and work efficiency including, e.g., ammonia known to correlate with the blood lactate contents. Local peaks of ammonia and lactic acidosis may provoke metabolic changes in the sub-maximal intensity trainings. Many researchers appreciate benefits of a few modern agents with the physical efficiency and stress tolerance boosting secondary effects. Agents with a hypoammonium effect (such as ammonium carbonate, aspartic acid salt, glutamate sodium etc.) are considered promising for their ability to boost stress tolerance. The study analyzes benefits of modern Hepamerz hepatoprotector that includes salts of aspartic acid and sodium glutamate as the key active substances. Hepamerts was tested with a detoxification effect due to the excessive ammonia being effectively removed. In addition, the preparation was tested to contribute to the Krebs ornithine urea cycle as it activates the cycle, restores the activity of the liver cell enzymes (ornithine-carbamoyl transferase and carbamoyl phosphate synthetase); facilitates the insulin and somatotropic hormone generation processes, and improves the protein metabolism.